A commonly used ecto‐ATPase inhibitor, ARL‐67156, blocks degradation of ADP more than the degradation of ATP in murine colon. Issue 9 (5th April 2016) - Durnin, L.; Moreland, N.; Lees, A.; Mutafova‐Yambolieva, V. N.
Abstract: Background: Adenosine 5′‐triphosphate (ATP) is released extracellularly as a neurotransmitter and an autocrine or paracrine mediator in numerous systems, including the gastrointestinal tract. It is rapidly degraded to active and inactive metabolites by membrane‐bound enzymes. Investigators frequently use inhibitors of ATP hydrolysis such as ARL‐67156 and POM‐1 to suppress the catabolism of ATP and prolong its effects in pharmacological studies. Our aim was to investigate directly the effects of ARL‐67156 and POM‐1 on the degradation of ATP and adenosine 5′‐diphosphate (ADP) in mouse colonic muscles. Methods: The degradation of ATP and ADP was evaluated by superfusing tissues with 1, N 6 ‐etheno‐ATP (eATP) and 1, N 6 ‐etheno‐ADP (eADP) as substrates and monitoring the decrease in substrate and increase in products (i.e., eADP, eAMP, and e‐adenosine) by high‐performance liquid chromatography techniques with fluorescence detection. Relaxation responses to etheno‐derivatized and non‐derivatized ATP and ADP were examined in isometric tension experiments. Key Results: ARL‐67156 inhibits the degradation of ADP but not of ATP, whereas POM‐1 inhibits the degradation of ATP but not of ADP in murine colonic muscles. Consequently, ARL‐67156 enhances relaxation responses to both ATP and ADP, whereas POM‐1 reduces relaxation to ATP and does not affect relaxation to ADP. Conclusions & Inferences: Studies that use ARL‐67156 to inhibit ATP degradation in smooth muscle likely evaluate responses to accumulated ADP rather than ATP. POM‐1 appears to be a more selective inhibitor of ATP degradation in the mouse colon. The choice of pharmacological tools in studies on extracellular ATP signaling may affect the interpretation of experimental data in functional studies. Abstract : ARL‐67156, at a concentration commonly used in physiological/pharmacological studies, does not inhibit the degradation of ATP, but rather causes accumulation of ADP. POM‐1 appears to be a better inhibitor of ATPases in the murine colon.